ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP MINAT WISATA DAN IMPLIKASINYA PADA STRATEGI PEMASARAN DI KABUPATEN BREBES - Ulul Absor; Sri Rahayu (Jurnal Strategik, 2019)
This study is entitled Analysis of Factors Affecting Consumer Behavior on Tourist Interest and Its Implications on Marketing Strategies in Brebes Regency. The aim to be achieved is to find out whether there is an influence between attitudes and subjective norms on the interests and behavior of consumers in Brebes Regency in enjoying tourism objects in Brebes Regency, to find out whether there is an influence between attitudes or subjective norms on consumer interests and behavior in enjoying attractions in Brebes Regency and to find out how much influence attitudes and subjective norms on consumer interests and behavior in Brebes Regency in enjoying tourist attractions. The research method used is the distribution of questionnaires using accidental sampling method as many as 100 tourists who visit tourist attractions. The results of the study can be explained as follows: T test results using 95 percent confidence level (α / 2 = 0.05 / 2 = 0.025) and degrees of freedom Nk (100-2) obtained a table of 2.2764 and the calculation results showed X1 = 4.274 which means that t count > t table . This shows that Ho is rejected or the attribute significantly influences the behavioral interest of visitors to the Tirta Husada Hot Spring Tourism Object, Cipanas Buaran Hot Spring Tourism Object, Malahayu Reservoir Tourism Object and Randusanga Indah Beach Tourism Object. While  at  X2, 1,386 is  obtained,  which  means  that  t count  < t table. This shows that Ho is accepted or subjective norms significantly do not affect the behavior of visitors to the Tirta Husada Hot Spring Tourism Object, Cipanas Buaran Hot Spring Tourism Object, Malahayu Reservoir Tourism Object and the Randusanga Indah Beach Tourism Object. The results of the F Test conducted using a 95 percent confidence level (α = 0.05) and df = n - k - 1 obtained Ftable of  3.09. While the results of calculations on each tourist attraction show 17,339. This shows that Fcount > F table which interpreted the Ho hypothesis is rejected which means that together the independent variable attributes and subjective norms affect the variable of interest in the behavior of visitors to the Tirta Husada Hot Spring Tourism Object, Cipanas Buaran Hot Springs Tourism Object, Reservoir Tourism Object Malahayu and Randusanga Indah Beach Tourism Objects.Keyword :  Consumer Behavior, Tourist Interest